Optimisation of storm water purification in progressive freeze concentration: stirring speed and initial concentration / Farah Hanim Ab Hamid and Nur Asyida Mohd Asyrul - Ab Hamid, Farah Hanim; Mohd Asyrul, Nur Asyida (Universiti Teknologi MARA, 2021)
A method has been earnestly studied which is progressive freeze concentration (PFC). In this study, zinc chloride dissolved in distilled water has been used to signify stormwater as its amount is the highest and high toxicity in actual stormwater. Response surface methodology (RSM) was employed to determine the optimum condition of the process. The experiment was run by using the data generated from STATISTICA software with constant coolant temperature and rotation time which is at −8 °C and 15 minutes. The interaction between the process conditions gave significant effects to the effective partition constant (K) and solute recovery (Y). The predicted optimum condition for the system within the experimental ranges would be a stirring speed of 245 rpm and initial concentration of 6.846 mg/L with the best value for K and Y are predicted at 0.3357 and 0.5856, respectively. Shortage of clean water supply, flooding and excessive stormwater runoff became a concern towards the human being as these problems cannot be simply solved by building a specific pipeline system. Thus, an excellent approach and process needed to manage and purify the stormwater as well as transform it as one of the clean water resources.